Do Men and Women Know What They Want? Sex Differences in Online Daters' Educational Preferences. (August 2018) - Whyte, Stephen; Chan, Ho Fai; Torgler, Benno
Using a unique cross-sectional data set of dating website members' educational preferences for potential mates ( N = 41, 936), we showed that women were more likely than men to stipulate educational preferences at all ages. When members indifferent to educational level were excluded, however, the specificity of men's and women's preferences did differ for different age groups. That is, whereas women expressed more refined educational preferences during their years of maximum fertility, their demand specificity decreased with age. Men's specificity, in contrast, remained stable until the 40s, when it was greater than that of postreproductive women, and then was higher during their peak years of career-earnings potential. Further, when individuals' level of education was controlled for, women (compared with men) were more likely to state a higher minimum preference for educational level in a potential mate.